(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Concrete is the most widely used material in the building sector. Every year, hundreds of millions of cubic meters of concrete are utilized in India alone. Concrete is composed up of coarse and fine particles that have been cemented together using binding material. The typical concrete process in the construction industry is unsustainable since it consumes large amounts of natural resources such as sand, stone, and millions of tons of cement each year, which is harmful to the environment. Aggregate accounts for 70- 80% of the volume of concrete and has a considerable impact on its various properties. Even industrialized countries have suffered aggregate supply constraints as a result of the significant growth in concrete demand across the world. As a result, research is needed to identify an environmentally benign and readily available alternative to the usage of component elements in concrete. Slag is a by-product of the steel industry, created by impurities in the metals or ores being processed during smelting, welding, and other metallurgical and combustion operations. Slag is generally made up of mixed oxides of elements including silicon, Sulphur, phosphorus, and aluminium ash, as well as byproducts of their interactions with furnace linings and fluxing materials like limestone. According to estimates, around one thousand million tonnes of slag is created as solid waste in India alone, necessitating study into how to use this large byproduct of the steel industry, which is not recyclable, as one of the elements in concrete manufacturing. Steel slag in construction protects natural aggregates while also using slag waste from steel mills, resulting in a higher reduction in environmental pollution. The use of steel slag as a partial substitute for fine aggregate in different concrete mixes where varying percentages of cement have been replaced by fly ash and metakaolin is recommended in this study. The effect of increasing the proportion of steel slag on various parameters was researched and compared, as were tests on compressive strength, tensile strength, and water absorption.